A circular equivalent planar array configuration for 5.8 GHz radar application - Asadullah, G. M.; Islam, Md. Rafiqul; Islam, Md. Shazzadul; Mahfuz, M.M. Hasan (2020)
As the spectrum demand increasing with time, so, the directivity and efficiency of antenna array now become a vital issue. Mostly, researchers have used a planar antenna array to get a high directive antenna with better performances. However, the planar array’s gain is limited. It contributes high sidelobe levels and strong mutual coupling effects those need to overcome. In this paper, a new configuration of 4 elements circular equivalent planar array has been proposed to achieve high gain and directivity with lower sidelobe level. After being designed and simulated, the proposed antenna array has achieved high directivity of 15.3 dBi with 85 % radiation efficiency. Besides, the array has a maximum realized gain of 14.51 dB and low sidelobe level of – 15.1 dB. In turn, the high directivity of the proposed antenna array resonating at 5.8 GHz with very minimum return loss makes it suitable for Radar application